The Effectiveness of Financial Accounting Information System with Approach of Organizational Culture and User Competency in Baznas North of West Java - ., Nurhayati; Nurhayati, N; Koesdiningsih, N (KnE Social Sciences, 2018)
The phenomenon that occurs at the moment in Indonesia that the implementation of AISs organized by BAZNAS is still not effective as disclosed by M. Fuaz Nasar, BAZNAS Deputy Secretary, who stated that the Zakat Reporting System is not integrated yet based on national Real Data, therefore, the zakat collection and distribution system of all Indonesia must be strengthened by appropriate mechanism, which is accountable and easily accessible to the community. This study aims to discover the influence of organizational culture and user competence on effectiveness of Accounting Information System (AISs) in the North West Java BAZNAS Indonesia. This study used explanatory research, correlational Analysis and hypothesis test used multiple regression. The findings for this study are: organizational culture significant positively affects 85.2% the effectiveness of Accounting Information System (AISs) in BAZNAS the North West Java, and user competence significant positively affects 78.3% of the effectiveness of Accounting Information System (AISs) in BAZNAS the North West Java. The results of this study can be generalized rather than those of previous studies. Keywords: Accounting Information System (AISs), BAZNAS, information systems, organizational culture, user competency